Ultrasonography assisted estrus detection improves the submission rate in prostaglandin treated sub-estrus Murrah buffaloes - Patra, Manas Kumar; Rajput, Atul Singh; Sasidharan, Jisna Kuttiyeri; Raza, Rehan Ahmad; Puttanarsappa, Thejaswini Meda; Lokavya, Athidi; Tomar, Atul Kumar Singh; Das, Goutam Kumar; Ghosh, Subrata Kumar; Gaur , Gyanendra Kumar (The Indian Journal of Animal Reproduction, 2023)
Sub-estrus is a condition in buffalo in which the ovarian picture and uterine changes suggest the presence of estrus and cyclicity, despite the absence of behavioural symptoms. The current study describes the effects of ultrasonography (USG)-aided estrus detection on submission and conception rate in sub-estrus Murrah buffaloes after a single shot of prostaglandin (PG) treatment. The study included 67 sub-estrus buffaloes between 2020 and 2021. The teaser bull was used to detect estrus, and the diameter of the pre-ovulatory follicle (POF) and corpus luteum (CL) was measured using transrectal USG. A single PG treatment induced behavioural estrus in 43.28% buffaloes (Gr. 1), while estrus were detected in 35.8% of sub-estrus buffaloes using sonographic examination (Gr. 2) that were otherwise remained undetected. The overall submission rate was 79.1 percent. The first-service conception rate was higher in Gr. 1 (55.2 vs. 33.3%), compared to Gr. 2. The CL diameter at pre-treatment was significantly larger in Gr. 1 buffaloes than in Gr.2 buffaloes. However, the POF diameter was comparable during induced estrus. Furthermore, the time elapsed between induction and breeding in both groups was comparable. Furthermore, the CL size at pre-treatment, POF size at estrus, and time elapsed to breeding had no effect on conception. Thus, the use of USG improves the submission rate in PG administered sub-estrus buffaloes, resulting in a 45.3% overall first service conception rate. However, breeding time must be optimised in order to improve the conception rate and efficient reproductive management in sub-estrus buffaloes in the field.
Keywords: Sub-estrus; Buffalo; Ultrasonography; Estrus induction; Prostaglandin; Preovulatory follicle size